KOORDINASI DALAM PENDISTRIBUSIAN GAS LIQUEFIED PETROLEUM GAS (LPG) 3 KG DI KOTA PEKANBARU - Octavia, Liny; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The need for LPG gas, nowadays, being a very important needs in life, whether in the household or in the bisnis development. Besides decrease in economical, LPG also become one of these targets the government to replace the use of kerosene in society, namely by conversion program of kerosene to LPG 3 kg. for people who low levels of economic and micro businesses. Pekanbaru City, since in 2009, including the carrying out of the program. This distribution of LPG 3 kg gas requires a clear and explicit coordination. The purpose of this research is to find out how coordination in distributing gas LPG 3 kg in the city of Pekanbaru and to know what factors affect coordination in distributing gas LPG 3 kg.In theory Hasibuan, there are 4 (four) indicator of coordination, namely: the division of work, discipline, communication and unity of action.Research method used in this research is research qualitative. With technique done; namely snowball sampling, to key informer on this research is dept. of industry and trade and pertamina and informer appendages is agent LPG 3 kg. And this research result analysis and managed with techniques used.Based on the research that has been conducted, the results of this study indicate that coordination in distributing gas LPG 3 kg has done is still not going well. There are some indicators that are still not walking by the unity which shows that there is coordination. Factors that affect coordination in distributing this is a managerial hierarchy in the distribution mechanisms, procedures and applicable rules and plan and purpose that have been made in the distribution of gas LPG 3 kg.Keywords: Coordination, Distribution, Liquefied Petroleum Gas